Design and Numerical Analysis of a Single-Polarization Filter Based on PCF with Plasmonic Layers of Gold and Indium Tin Oxide - Owusu Mensah, Isaac; Akowuah, Emmanuel Kofi; Danlard, Iddrisu; Amoah, Alexander Kwasi (International Journal of Optics, 2022)
This paper presents a single-polarization filter based on PCF with plasmonic layers of gold and indium tin oxide (ITO). The plasmonic materials are metallic gold and ITO coated on the inner walls of two extra-large vertically arranged air holes. The resonance effect is triggered by guided modes propagating through the silica core and coupling to the coating areas. The finite element method is used to analyze the properties of the filter for the two fundamental orthogonal polarizations. A filtering effect is achieved in the communication window by optimizing the structural factors as well as gold film and ITO deposition thicknesses. When the filter is 1 mm long, the obtained filtering effect is 1319.689 dB/cm for the y-polarization and 31.881 dB/cm for the x-polarization, thus efficiently attenuating the y-component at a communication window of 1.15 μm. With a filtering bandwidth of 602 nm, the proposed filter shows superior characteristics compared with previously reported results. Applications of the proposed plasmonic PCF-based filter can be found in polarization-maintaining and polarization-suppressing systems for optical sensing and broadband transmission.